Synthesis of Silver Nanoparticles by Reduction of Silver Ion with m-Hydroxybenzoic Acid - Gusrizal, Gusrizal; Santosa, Sri Juari; Kunarti, Eko Sri; Rusdiarso, Bambang (Asian Journal of Chemistry, 2017)
In this study, we demonstrated the use of m-hydroxybenzoic acid in the synthesis of stable silver nanoparticles (AgNPs). Besides working as a reducing agent, m-hydroxybenzoic acid also simultaneously played a role as a capping agent. In the synthesis of AgNPs, silver nitrate was first mixed with the pH-adjusted m-hydroxybenzoic acid solution. The mixture was then heated in a boiling water bath. The formation of AgNPs was indicated by the appearance of yellow colour usually completed in 15 min. The reducing ability of m-hydroxybenzoic acid was affected by its pH and concentration. At a mole ratio of silver nitrate and m-hydroxybenzoic acid 1:10, the reaction produced AgNPs with the average size of 19 ± 9 nm. Stability test over a period of 18 weeks showed that AgNPs were highly stable with the intensity of surface plasmon resonance peak only reduced 2.0 %. This experiment indicates the potency of AgNPs.